ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA OTONOMI KHUSUS DAN BELANJA MODAL TERHADAP PDRB DI KAB/KOTA PROVINSI PAPUA - Ade Rosita Dwi Anwar; M Faisal Abdullah; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to see the development of local revenue, special autonomy funds and capital expenditure of each Kota District in Papua Province. And see the effect of Local Revenue, special autonomy fund and capital expenditure to Gross Regional Domestic Product of Regency / City of Papua Province. The analysis tool used is multiple regression with panel data during the period of 2011-2015. Result of research with selected model Fixed Effect Model show that variable of original revenue area have positive and significant effect with coefficient equal to 0.076579, Special Autonomy Fund have positive and significant influence with coefficient equal to 0.077388, Capital Expendancy has negative and significant effect with coefficient equal to -0.023542. while the value of the coefficient of determination is 0.822726 Or 82%, it indicates that the ability of variable local revenue, special autonomy fund and capital expenditure in explaining the gross regional domestic product of 82%.keywords: Gross regional domestic product, local revenue, special autonomy fund and capital expenditure